Comparison of endogenous GHB concentrations in blood and hair in death cases with emphasis on the post mortem interval - Castro, André Lobo (2016)
Gamma-hydroxybutyric acid (GHB) is an endogenous compound which has a story of clinical use and illicit abuse since the 1960’s. The possibility to use a multi-sample approach of GHB evaluation, including whole blood and hair, to better characterize a forensic toxicology case and evaluate a possible causal association with the death, is an exciting up-to-date issue. In addition, its post-mortem behaviour, namely regarding degradation and metabolism, has been increasingly investigated as a putative biomarker for post-mortem interval (PMI) estimation. Thus, In order to contribute to clarify this specific aspect, whole blood and hair post-mortem GHB levels were evaluated in thirty two real cases with previous information on death and autopsy data. The results obtained suggest that the PMI (until 5 days between death and sampling) influences GHB whole blood concentration, but not GHB levels in hair samples. No differences were encountered for the other parameters evaluated, including age, gender, cause of death and presence or absence of substances. This study brings new insights regarding the usefulness of GHB levels in forensic toxicology, which might be further strengthened with larger, but comparable, studies from other laboratories and institutions in the context of legal medicine.